In situ preparation of two-dimensional ytterbium ions doped all-inorganic perovskite nanosheets for high-performance visual dual-bands photodetectors. (March 2022) - Sun, Rui; Zhou, Donglei; Lu, Po; Jing, Xiaoling; Zhuang, Xinmeng; Liu, Shuainan; Wang, Yuqi; Bai, Xue; Xu, Wen; Song, Hongwei
Abstract: Two-dimensional (2D) all-inorganic halide perovskites exhibit impressive optical and electrical properties, which are attracting extensive current interests. Rare earth (RE) ions doping is a significant method to adjust their optical, electrical properties and realize various applications. However, 2D RE ions-doped perovskite crystals have been rarely reported. Herein, we reported the synthesis of novel 2D all-inorganic perovskite CsPbClx Br3−x nanosheets (NSs) doped with RE ions. The octylamine (OLAm) with short carbon chains is used to tune the growth orientation for the preparation of 2D perovskite NSs. The morphology of the NSs can be adjusted by varying the ratio of shorter ligands to longer ligands and changing the temperature. The Yb 3+ ions doped CsPbClBr2 NSs demonstrate an excitonic emission of perovskite host and a quantum cutting emission of Yb 3+ ions at 985 nm with the optimal photoluminescence quantum yield (PLQY) of 128%. The results of femtosecond time-resolved transient absorption spectroscopy and DFT calculations indicate that the defect density of NSs is largely decreased and the photostability is enhanced induced by the passivation effect of Yb 3+ ions. The photodetector (PD) based on lateral assembled Yb 3+ ions doped CsPbClBr2 NS film is fabricated, which demonstrates a high responsivity and dual-band detection capability. The as-fabricated PDs are sensitive to both UV and NIR light, showing the responsivity of 1.96 A W −1, 0.12 mA W −1, the detectivity of 5 × 10 12, 2.15 × 10 9 Jones at 440 nm and 980 nm, respectively. Finally, based on an imaging system with a PD array and a data analysis system, visual photoelectric detection is realized, and high-contrast images of the measured UV and NIR light are displayed. This work paves the way to tune the properties of 2D perovskite materials and develop high-performance optoelectronic devices. Graphical Abstract: In this work, a modified hot-injection method was demonstrated to synthesize the all-inorganic CsPbX3 (XCl, Cl/Br) perovskite NSs doped with Yb 3+ ions, realizing more effective quantum cutting of Yb 3+ ions with PLQY of 128%. Eventually, PDs based on the laterally assembled Yb 3+ doped NS film were fabricated, which can realize multi-band detection and distinction of UV and NIR light. Moreover, the UV light imaging system was designed, which can collect the detection signal from the PD array and display the image. ga1 Highlights: ● Yb 3+ doped CsPbX3 nanosheets are synthesizedPhotodetectors can detect and distinguish UV, NIR lightVisual photoelectric detection is realized. ● The photodetectors based on Yb 3+ doped nanosheet film showed the ability to detect and distinguish the UV and NIR light. ● The UV light imaging system was designed, which can collect the detection signal from the photodetector array and display the image.